Impact of clopidogrel and potent P2Y12-inhibitors on mortality and stroke in patients with acute coronary syndrome or undergoing percutaneous coronary intervention - Aradi, Dániel; Komócsi, András; Vorobcsuk, András; Serebruany, Victor L. (Thrombosis and Haemostasis, 2013)
Administration of a P2Y12-receptor antagonist in addition to aspirin is mandatory in patients with acute coronary syndromes (ACS) or undergoing percutaneous coronary intervention (PCI) to reduce the occurrence of thrombotic events; however, their impact on mortality and stroke is unclear. We aimed to evaluate the influence of moderate (clopidogrel) or potent (prasugrel/ticagrelor) P2Y12-receptor inhibition on major cardiovascular outcomes among patients with ACS or undergoing PCI. Systematic literature search was performed to find randomised, controlled clinical trials comparing the clinical impact of clopidogrel with placebo or prasugrel/ticagrelor versus clopidogrel. Outcome measures included cardiovascular death, myocardial infarction (MI), total stroke and intracranial haemorrhage (ICH). Random-effects model with Mantel-Heanszel weighting was used to pool outcomes into a meta-analysis. Four studies comparing clopidogrel with placebo and five trials comparing clopidogrel with new P2Y12-receptor inhibitors were identified including a total of 107,473 patients. Compared to placebo, clopidogrel reduced the risk of cardiovascular death (odds ratio [OR]: 0.93; 95% confidence interval [CI]: 0.87–0.99, p=0.02), MI (OR 0.80; 95%CI 0.74–0.88, p<0.00001) and stroke (OR 0.84; 95%CI 0.72–0.97, p=0.02), without influencing risk for ICH (OR 0.96;& 95%CI 0.69–1.33, p=0.79). Treatment with prasugrel/ticagrelor provided additional benefit over clopidogrel regarding cardiovascular mortality (OR 0.86; 95%CI 0.78–0.94, p=0.002) and MI (OR: 0.83; 95%CI 0.74–0.93, p<0.001), but no advantage in stroke (OR: 1.06; 95%CI 0.88–1.26, p=0.55) and in ICH (OR: 1.16; 95%CI 0.75–1.81; p=0.49) was observed. Increased potency of P2Y12-receptor inhibition is associated with decreased risk in cardiovascular death and MI; however, this association is not true in case of stroke, where potent P2Y12-receptor antagonists have no incremental benefit over clopidogrel.
Keywords: Stroke; clopidogrel; prasugrel; ticagrelor; P2Y12-receptor; platelet inhibition